2015
DOI: 10.5539/gjhs.v7n4p211
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Educational Environment of a Nursing School by Using the DREEM Inventory

Abstract: Background:Educational Environment (EE) is considered as a key component of educational curriculum.Aim:The aim of this study was to evaluate the EE of Nursing and Midwifery School of Tehran University of Medical Sciences (TUMS) by using Dundee Ready Education Environment Measure (DREEM).Methods:This cross-sectional descriptive study was conducted in 2013. Totally, 500 nursing or midwifery students were recruited to the study by using the quota sampling method. Study data were collected by using a demographic q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 17 publications
2
19
1
1
Order By: Relevance
“…Out of a total score of 200, the mean DREEM score of the total sample of nursing students was 111 (25) ( Table 3 ). This score fell within the “more positives than negatives” category ( Table 1 ), and is in line with scores in studies from Iran, 6 , 9 India, 13 Indonesia, 12 Malaysia, 10 Chile, 7 and the United Kingdom, 11 which ranged between 104 and 138. Such scores indicate an acceptable learning environment that may benefit from some improvement for the sake of quality assurance.…”
Section: Discussionsupporting
confidence: 82%
“…Out of a total score of 200, the mean DREEM score of the total sample of nursing students was 111 (25) ( Table 3 ). This score fell within the “more positives than negatives” category ( Table 1 ), and is in line with scores in studies from Iran, 6 , 9 India, 13 Indonesia, 12 Malaysia, 10 Chile, 7 and the United Kingdom, 11 which ranged between 104 and 138. Such scores indicate an acceptable learning environment that may benefit from some improvement for the sake of quality assurance.…”
Section: Discussionsupporting
confidence: 82%
“…According to standard interpretations of DREEM subscale scores, the mean score for the perceptions of learning subscale in the current study was deemed Other studies from the Middle Eastern region have addressed students' perceptions of the educational environment at various medical colleges [ Table 4]. 11,[21][22][23][24][25][26][27][28][29][30][31][32][33] In general, the scores of medical schools in previous studies from 2004-2010 were much lower compared to those reported from more recent studies. 11,[21][22][23][24][25][26][27][28][29][30][31][32][33] This observation suggests that significant improvements have been made to the learning environments of medical schools in the region.…”
Section: Discussionmentioning
confidence: 99%
“…Literature review of recent studies using the Dundee Ready Education Environment Measure tool at institutions in the Middle East11,[21][22][23][24][25][26][27][28][29][30][31][32][33] …”
mentioning
confidence: 99%
“…[24][25][26] The DREEM has five major domains of student's self-perceptions regarding: learning, teachers, atmosphere, academic, and social climate and it has been used by various nursing educational institutions. [27][28][29][30] Since the integrated nursing educational environment remains to have a crucial influence on the student achievement, behaviors, satisfaction and success, which necessitates, the need to receive a detailed feedback from nursing students regarding their both clinical and academic experiences, especially in highly stressful critical care clinical learning settings, in order to provide a beneficial guide for strategic planning, resource utilization as well as corrective actions of negatively perceived students' concerns for future academic improvement. [15,31] Many researches mainly emphasized on the clinical environment and student perceptions without investigating the relationship between their perceptions and academic outcomes.…”
Section: Introductionmentioning
confidence: 99%